ANALISIS STRATEGI PENGHIMPUNAN DANA (FUNDING) BANK MUAMALAT INDONESIA KCP SUKABUMI DALAM MENINGKATKAN DAYA SAING PERBANKAN SYARIAH - Risna Nurul Insani; Abdul Muhyi; Moch Salman Alfarizi; Ihsan Nultam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In an effort to enhance competitiveness in the Islamic banking industry, this study investigates the fundraising strategy of PT Bank Muamalat Indonesia Tbk. KCP Sukabumi. Data were collected through banking operation documentation, field observations, and in-depth interviews using descriptive qualitative research methods. The results show that Bank Muamalat KCP Sukabumi uses an integrative strategy to increase Current Account Saving Account (CASA) through savings and checking products based on Wadiah and Mudharabah contracts. This is optimized through digital transformation with the Muamalat DIN application, institutional collaboration, and a community-based marketing approach that leverages the strong religious base in the Sukabumi region to achieve this goal. Although the bank is known as a pioneer of pure Islamic banks, according to a SWOT analysis, their limited physical infrastructure and intense competition from large banks and digital entities. This fundraising strategy has proven very beneficial in reducing funding costs, maintaining liquidity stability, and strengthening customer loyalty through spiritual and emotional approaches. According to this study, to maintain competitive advantage and sustainable profitability in the local and national financial markets, Bank Muamalat must strengthen its digital ecosystem and improve Islamic financial literacy.